Damage constitutive model and mechanical properties of a concrete limestone composite after acid corrosion - Jie Wang; Bin Du; Mingxuan Shen; Yukun Li; Shisong Yuan (Scientific Reports)
Abstract Long-term erosion by acidic solutions in karst regions leads to continuous deterioration of the physical and mechanical properties at the interfaces of engineering structures, adversely affecting their operational performance. To investigate the degradation patterns of the mechanical properties and corrosion mechanisms of the concrete‒limestone composite (CLC) after exposure to acidic corrosion, three kinds of CLC samples treated with acidic solutions of different pH values were fabricated. Mechanical property analysis was conducted via triaxial compression testing methods. Lemaitre’s strain equivalence hypothesis was utilized, and on the basis of the assumption that the strength of rock microelements follows a Weibull distribution, the damage to microelements due to acidic corrosion was combined with compressive failure. The study results indicate that acidic corrosion significantly affects the mechanical properties and failure modes of CLCs. As the pH of the solution decreased from 7 to 5 and then to 3, the peak strengths of the samples decreased by 16.6% and 11.92%, whereas the elastic moduli decreased by 25.36% and 23.13%, respectively. Furthermore, with increasing confining pressure, the peak and residual strengths of the composite significantly improved; the residual strength increased from 8.2 MPa to 86.93 MPa as the confining pressure increased from 0 to 10 MPa. Finally, by introducing a damage constitutive model corrected for postpeak residual strength, the stress‒strain full-process curves of CLCs under different degrees of acidic corrosion were more accurately simulated. The validation results confirm the applicability and accuracy of the established model, providing a theoretical basis and technical support for understanding and predicting the mechanical behavior of limestone–concrete structures in acidic environments.